Effects of Brand Image and Satisfaction on Patient Loyalty with Family Support Moderation - Ratu Suciangraini Hasibuan; Muryati Muryati; Muchlis Mas'ud (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study aims to analyze the influence of brand image and patient satisfaction on patient loyalty, with family support as a moderating variable in non-infectious inpatients participating in BPJS Kesehatan at RSUD Cengkareng, West Jakarta. Patient loyalty is a strategic aspect for hospitals in maintaining service sustainability, especially amidst the increasing needs and demands for health services. This study used a quantitative approach with a survey method. The study population was non-infectious inpatients participating in BPJS Kesehatan at RSUD Cengkareng, with a sampling technique using purposive sampling. Primary data were collected through the distribution of structured questionnaires to respondents who met the research criteria. Data analysis was performed using Structural Equation Modeling–Partial Least Square (SEM-PLS) to test the direct and moderating effects between variables. The results showed that brand image and patient satisfaction had a positive and significant effect on patient loyalty. In addition, brand image also had a positive and significant effect on patient satisfaction. Family support was shown to strengthen the relationship between patient satisfaction and patient loyalty, and moderate the relationship between brand image and patient loyalty with a relatively weak level of moderation. These findings emphasize the importance of strengthening hospital image, increasing patient satisfaction, and family involvement in healthcare services as strategies to build and maintain loyalty among inpatients participating in BPJS Kesehatan.